2011
DOI: 10.1007/s10561-011-9277-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment for processed and sterilized bone using Raman spectroscopy

Abstract: To eliminate the potential for infection, many tissue banks routinely process and terminally sterilize allografts prior to transplantation. A number of techniques, including the use of scanning electron microscopy, bone graft models, and mechanical property tests, are used to evaluate the properties of allograft bone. However, as these methods are time consuming and often destroy the bone sample, the quality assessment of allograft bones are not routinely performed after processing and sterilization procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
13
0
3
Order By: Relevance
“…Methods of sterilization such as heat [31,41,42,45,63], hydrogen peroxide [15,24] and ethylene oxide [47,57,65] can negatively affect allograft mechanical and biological properties. Heat treatment greater than 60°C reduces the strength [41,42,45,71,72] and impairs osteoinductivity [44]. Chemical treatments such as ethylene oxide and hydrogen peroxide also are harmful to osteoinductivity [8,15,24,25,54,56].…”
Section: Introductionmentioning
confidence: 99%
“…Methods of sterilization such as heat [31,41,42,45,63], hydrogen peroxide [15,24] and ethylene oxide [47,57,65] can negatively affect allograft mechanical and biological properties. Heat treatment greater than 60°C reduces the strength [41,42,45,71,72] and impairs osteoinductivity [44]. Chemical treatments such as ethylene oxide and hydrogen peroxide also are harmful to osteoinductivity [8,15,24,25,54,56].…”
Section: Introductionmentioning
confidence: 99%
“…2a) contains the Raman bands responsible for the mineral structure of bone matrix, such as 1 (PO 4 ) 3-vibrational mode in the molecule of hydroxyapatite at 956 cm -1 , 3 (PO 4 ) 3-at 1030 and 1045 cm -1 , 1 (CO 3 ) 2-(B type substitution where (PO 4 ) 3-a substituted (CO 3 ) 2-) at 1069 cm -1 and 1 (CO 3 ) 2-vibration mode (A type substitution where a substituted OH-(CO 3 ) 2-) at 1098 cm -1 [Yamamoto T. et al (2011), Crane N.J. et al (2013]. Band at 956 cm -1 is dominant by the intensity throughout all Raman spectrum of bone tissue, which determines the content of hydroxyapatite in bone matrix, and also possible to study the content of carbonate (CO 3 ) 2-in the process of demineralization.…”
Section: Resultsmentioning
confidence: 99%
“…Band at 956 cm -1 is dominant by the intensity throughout all Raman spectrum of bone tissue, which determines the content of hydroxyapatite in bone matrix, and also possible to study the content of carbonate (CO 3 ) 2-in the process of demineralization. Less intense bands at 816, 852, 920, 941 and 870 cm -1 corresponding to the stretching vibration of C-C in proline and hydroxyproline [Yamamoto T. et al (2011), Crane N.J. et al (2013], and the band at 1003 cm -1 responsible for C-C stretching vibration in phenylalanine [Crane N.J. et al (2013)] represent the organic component of bone matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voggenreiter et al [62] studied the bone surface structure of cortical bone grafts using SEM and observed no deleterious effects of cryopreservation and irradiation. Yamamoto et al [68] reported that the gamma irradiation of femurs to a dose of 25 kGy increased the crystallinity, whereas, there was no change in the Raman spectrum. The authors concluded that increased crystallinity may be due to the adverse effects of gamma radiation on bone allografts.…”
Section: Properties Of Tissuesmentioning
confidence: 99%